Post-reproductive lifespan in wild mountain gorillas - Smit, Nikolaos; Robbins, Martha M. (National Academy of Sciences, 2026)
Animals can typically maximize their fitness by reproducing throughout adulthood. Yet, in a handful of species, females cease reproduction long before death, highlighting an apparent evolutionary paradox. We used over three decades of life-history and behavioral data to examine the prevalence of postreproductive lifespan in wild mountain gorillas (Gorilla beringei beringei). Almost one third of females in our study population (7/25) have been “postreproductive” according to a commonly used criterion and have lived more than a decade past their age of last reproduction, representing at least a fourth of their adult lifespan. Additionally, using conservative estimates of female ages, we found a significant post-reproductive representation (a common population-level measure of post-reproductive lifespan) equal to 0.10. Our results add to observations of postreproductive lifespan in chimpanzees and humans and thus, they represent a critical addition to our understanding of hominid life-history evolution.